Cement leakage into the paravertebral venous system and pulmonary cement embolism following percutaneous vertebroplasty: a case report - Lai, Chengrong; Meng, Qingcun; Zhang, Honglei; Liu, Yanbin; Liu, Jinlong (Frontiers in Surgery, 2025)
Pulmonary cement embolism is a potentially serious complication following percutaneous vertebroplasty. The risk factors for pulmonary cement embolism have not been clearly identifed. Cement leakage into the azygos vein or in the inferior vena cava has been identifed as a risk factor for pulmonary cement embolism. In addition cement leakage into the paravertebral venous system also seems to be related to pulmonary cement embolism. Here we report a case with detailed preoperative data, intraoperative findings, and imaging evidence to demonstrate the relationship between cement leakage into the paravertebral venous system and pulmonary cement embolism. CaseA 69-year-old woman was diagnosed with osteoporotic vertebral compression fractures and treated with percutaneous vertebroplasty. Intraoperatively, anterior cement leakage into the paravertebral venous system was detected on lateral fluoroscopy but it did not cause insufficient attention. The patient demonstrated significant back pain relief postoperatively, and had no symptoms such as dyspnoea, coughing, haemoptysis, dizziness or palpitation. However, the postoperative thoracolumbar x-ray presented that multiple tubular and branching cement emboli were scattered throughout the lungs. The patient presented asymptomatically in the follow-up period. No cardiorespiratory dysfunction was observed until the end of the one-year clinical follow-up, and the patient was satisfied with pain relief.ConclusionCement leakage into the paravertebral venous system is associated with pulmonary cement embolism during percutaneous vertebroplasty. Continued bone cement injection after bone cement leakage into the paravertebral venous system is dangerous and, may lead to further migration and, ultimately, pulmonary cement embolism. Once bone cement leakage into the parav ertebral venous system is detected, percutaneous vertebroplasty should be terminated.